Perbandingan Perhitungan Sisa Cadangan Batu Granit Menggunakan Metode Cross Section Terhadap Metode Contour Pada PT Aditya Buana Inter Di Kabupaten Bangka: Comparison Of Calculation The Rest Reserve Of Granite Using Cross Section Method On Contour Method At PT Aditya Buana Inter In Bangka Regency - Irwan, Andesta Granitio; Irvani, Irvani; Guskarnali, Guskarnali (Program Studi Teknik Pertambangan Universitas Bangka Belitung, 2018)
The calculation of the remaining reserves is one of the important things in the world of mining, especially in the mining business of granite. The importance of the calculation of reserves is used to determine the potential of granite stone resources in determining the amount of production of the company and the age of the company. For that many methods of calculating the reserves that can be used according to the type of minerals to be calculated the remaining reserves one of them using Cross Section Method and Contour Method. Field measurement used theodolith which further processing done by making contour map using Software Surpac 6.6.2. Processing using Minescape 4.119 Software for Cross Section Method with contour map iterval 1, 5, and 10 m and in division section with interval section 10, 15, and 20 m so as to obtain the width of field section, while Contour Method used contour elevation map that is 1, 5, and 10 m so as to obtain the area of ​​the field between the same elevation. After obtaining the area of ​​each method, use the frustum equation and mean area to determine the volume of surface reserves and from the volume results can be known the length of the mine life. The results obtained from the processing is the method of Cross Section largest reserve calculation value is at contour 1 m with the interval section 10 m that is equal to 5.662.168,28 m3 or 14.721.637,53 tons, while the Contour Method of the largest reserve value is at a contour interval of 1 m ie 4,871,332,59 m3 or 12,665,464,73 tons and for the age of the mine obtained using the highest reserve value in the Cross Section Method has a longer mine life of 42 years, while in Contour Method is 41 years.